Sistem Pendukung Keputusan Karyawan Terbaik Dengan Metode Profile Matching Best Employee Decision Support System With Matching Profile Process Method - Yoga Religia (Jurnal SIGMA, 2020)
Promising human resources can support the advancement of a company. Human resource development must also have clear and well-planned rules. To maintain good resources and produce promising resources, management planning is needed, for example in the form of hiring new employees, conducting training, performance appraisal, etc. The process of selecting the best employees at PT Samudera Ocean Perkasa Indonesia which is still manual and accompanied by decision making takes a long time. So as to simplify the process of selecting the best employee recommendations, it is very necessary to build a decision support system so that it can help to provide the best employee selection recommendations. In this study the problem was formulated about how to implement the profile matching method for the selection of employees in PT Samudra Ocean Perkasa Indonesia. While the aim of this research is to choose the best employees in PT Samudra ocean mighty Indonesia to be more targeted. The result of this application is the system automatically recommends the best employees, and testing this system using a blackbox, and after use the blackbox system is ready to use. Keywords : decision support system, Profile Matching, php.